Papua New Guinea Moho inversion based on XGM 2019e gravity field model - Liu, Yijun; Yang, Guangliang; Zhang, Jie; Zhao, Bingjie (Frontiers in Earth Science, 2023)
The construction of the Moho depth model is significant for studying the characteristics of the complex tectonic movement (seafloor spreading, plate subduction phenomena) in Papua New Guinea. We calculate the region's Moho relief using the XGM2019e gravity field model and nonlinear fast gravity inversion method under the GEMMA Moho depth model’s constraint considering the influence of lithosphere thermal gravity anomaly. The calculation result shows that the Moho depth is between 6~34 km, forming two large depressions in Woodlark Basin (WB) and Solomon Sea Plate (SSP) with deep scattered islands. In addition, the findings suggest that Significant differences exist in the shape and tectonic movement intensity of the North and South oceanic crust at the WB. Nevertheless, the lithosphere extends evenly in Manus Basin (MB). WB collided with the Solomon Islands at a higher angle than the SSP subducted under Bismarck Sea Plate (BSP); strong earthquakes may frequently occur on both sides and in deeper positions at West New Britain Trench in the future.